The impact of an unconditional parental benefit on employment of mothers: A comparative study of Estonia and Lithuania. Issue 1 (14th March 2017) - Kurowska, Anna
Abstract : Purpose: The purpose of this paper is to solve the puzzle of the disproportionately lower employment rate of mothers of toddlers with relation to the employment rate of mothers of preschool and school-age children in Estonia. Design/methodology/approach: The research is based on the Most Similar System Design and compares Estonia with Lithuania. The applied methods include inferential statistics and microsimulation techniques, employing the OECD Benefits and Wages Calculator, the OECD Family Support Calculator and EUROMOD – the European tax-benefit microsimulation model. Findings: The comparison revealed that the overwhelming majority of the crucial aspects of socio-cultural, economic and institutional conditions were more favourable for maternal employment in Estonia than in Lithuania. This explains the higher maternal employment rates both for mothers of pre-schoolers and school-age children in Estonia. However, one particular element of the institutional context targeted to the mothers of toddlers – the unconditional parental benefit – had an entirely opposite character. This particular feature of the parental leave scheme was the only factor that could explain why the employment rate of mothers of toddlers is disproportionately lower than the employment rate of mothers of older children in Estonia and much lower than the employment of mothers of toddlers in Lithuania. Originality/value: This study complements previous research by providing evidence on the relative importance of universal parental benefit schemes in the context of other country-specific conditions for maternal employment, including the availability of institutional childcare. Furthermore, the results presented show that childcare regime typologies, at least those that characterise Eastern European countries, should be more sensitive to children's age.